TEACHER-LEARNER INTERACTION IN COLLEGE AND ITS EFFECTIVENESS: AN ANALYTICAL STUDY - Gupta, Arti; Pal, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Effective teacher-student interaction is crucial in shaping the educational experiences and outcomes of college students. The purpose of this study is to explore the nature, patterns, and impact of interactions between college teachers and students, focusing on how these interactions affect student learning, motivation, and overall academic success. Using secondary data from various scholarly articles, educational reports, and case studies, the research highlights key interaction dimensions, including communication styles, feedback mechanisms, and emotional support. The study shows that positive, constructive, and frequent interactions lead to better engagement, deeper understanding, and student satisfaction. In contrast, limited or negative interactions hinder academic performance and reduce motivation. The analysis emphasizes the role of active listening, empathy, and clarity in teacher communication, which are essential for promoting a supportive learning environment. In addition, the study discusses the challenges teachers face in maintaining effective interactions, such as large class sizes and time constraints. Recommendations include adopting a student-centred approach, incorporating technology for better communication, and training teachers to develop interpersonal skills. Overall, this paper contributes to the understanding of how improving teacher-student interactions can lead to more effective teaching strategies and better educational outcomes in higher education settings.